The relationship between cultural beliefs and treatment-seeking behaviour in Papua New Guinea: implications for the incorporation of traditional medicine into the health system - Macfarlane, Joan (Curtin University, 2005)
Health indicators in Papua New Guinea (PNG) are poor by virtually any standards and have declined over the last 2 decades. As in other developing countries that find it impossible to achieve ‘health for all’ through western medical services alone, the idea of developing an integrated health system, one that incorporates traditional medicine, has been proposed as a way of addressing poor health status. The idea of developing an integrated health system in PNG is not new but only recently has it translated into action with tangible results including a draft ‘National Policy on Traditional Medicine for Papua New Guinea’. Over many years researchers have bemoaned the paucity of information on cultural beliefs and treatment practices that could make the incorporation of traditional medicine into the health system, along the lines proposed in the National Policy, better informed. To date this information gap has not been filled.The thesis includes a review of literature on traditional medicine around PNG and the results of a case study conducted by indigenous research assistants among the Nasioi speakers of Central Bougainville. An international perspective is brought to bear through a critique of theoretical models of integration and a review of practical experiences in other countries that have tried to develop various types of integrated health systems. Information from each of these sources is considered in an endeavour to address the urgent need for information to inform the implementation of the National Policy on Traditional Medicine for Papua New Guinea.All available studies on traditional medicine in PNG were included in the literature review. Despite PNG's vast cultural diversity it became evident that some common elements exist between different cultural groups.The case study used a focused ethnographic approach to examine treatment-seeking responses to illness and associated beliefs and decision-making criteria in relation to traditional and modern medicine. It also investigated the organization of traditional health services, attitudes towards an integrated health system and the potential for practitioners to collaborate with one another. The case study made it possible to focus on pertinent issues that had not been covered in earlier studies. The case study suggests that in areas where the organization of and attitudes toward traditional medicine resemble those in the Nasioi area there may be great potential for a health system that incorporates traditional medicine to deliver health benefits to communities. The case study also serves as an example of research that could be replicated or adapted by provinces that need more information about their own situation before embarking on the process of incorporating traditional medicine into the local health system.The process by which integration might proceed in PNG is considered in the context of integration experiences in other countries. Although ideologically attractive, total integration is not realistic for PNG at this stage. The informality and lack of documentation on traditional medicine as well as the lack of resources to support the development of an integrated health system mean that PNG’s own version of an incorporated or collaborative model of integration is more appropriate.It should be noted that in this thesis the term ‘integrated health system’ is used to cover the full range of varying degrees of integration of traditional with modern medicine and should not be taken to imply only a fully integrated system. Similarly, the terms ‘integration’ and ‘incorporation’ are normally used to refer to the process and not the outcome.Even an incorporated health system may not be a viable proposition in all parts of PNG. Where it is feasible, incorporation would need to be progressed in a carefully considered and planned manner with a realistic and long-term approach. The process would require coordination at national level and the flexibility for provinces to participate according to their own prevailing circumstances and capacity. Incorporation should proceed slowly and will require government support including the allocation of resources. It may be possible to pilot and thus fine-tune PNG’s integration model in a few places, such as the Nasioi area, before expanding to multiple provinces.The potential benefits of an incorporated health system include strengthening of primary health care, better access to services, more affordable services, cultural relevance, a holistic approach, preservation of traditional knowledge, increased autonomy and possibly cost savings. An incorporated health system is worth pursuing because, if carefully planned and implemented, it does have the potential to improve health status in a country where health indicators desperately need to be elevated.